Онтологічний аналіз біометричних даних - Вербицький, Євген Володимирович; Ларін, Дмитро Анатолійович (НТУ "ХПІ", 2017)
Описано перспективи використання переносних бездротових давачів для моніторингу життєво важливих показників організму. Запропоновано концепцію платформи для обробки та аналізу біометричних даних і взаємодії з мережевими вузькоспеціалізованими сервісами, що надають рекомендації щодо підтримання здоров’я на належному рівні, профілактики та лікування захворювань і прогнозування їх розвитку. Наведено принцип побудови системи, що базується на створенні онтологічної бази знань, що в компактній формі на основі виміряних числових біометричних даних описує стан здоров’я людини на основі та дає змогу на основі їх числових параметрів описати стан людини.

Development perspectives of wearable wireless sensors for monitoring health parameters are described. Possibility disease diagnostic improving with continuous noninvasive health monitoring with wireless sensors is shown. Automatisation diagnostic benefits in decreasing diagnostic time, cost and eliminating human factor is underlined. Specialized medical online software for disease diagnostic based on symptoms analysis are reviewed. A problem of biometric numerical data arrays transform to medical symptoms is shown. Platform conception for biometric data processing, analysis, and interaction with specialized n etwork services of health support recommendation, prophylaxis, and treatment of diseases and its prediction is proposed. Integration numerical data arrays into contextual data are proposed. Contextual data classes of human health based on temperature, cardiogram, and pulse are developed. A principle of system design based on the ontological knowledge base, which allows describing the human health state in a compact form with measured numerical biometric data is described. Classes of the ontological database are proposed. Numerical data classification for temperature, cardiogram and pulse is developed. The four layer structure of rule based on context types for human health estimation is proposed. Rules based on expert knowledge are developed. A rule example for otr classification is developed. The principle of choosing the most reliable scenario is proposed. Software platform interaction with different health supporting web-service is described. Data collection and processing features are considered.
Ontological analysis of biometric data
Keywords: моніторинг; бездротові мережі давачів; веб-сервіс; електрокардіограма; ЕКГ; wireless sensor networks; web-service